Avaliação da eficiência neuromuscular e do senso de posição articular do joelho em indivíduos com amputação transtibial - Costa, Cleber Soares Pimenta (2016)
Muscle strength, the position Sense of Articular (SPA) and postural balance are usually altered in amputated patients because the request and proprioceptive and functional responses depend on the sensory-neuro-motor system integrity. Little research has been developed with transtibial amputees, much less addressing the evaluations present in this study. The objectives of this study were to evaluate the Neuromuscular Efficiency (ENM), the Postural Stability and Spa knee of subjects with unilateral transtibial amputation, comparing the results with the contralateral limb and the control group. It was a cross-sectional study with a quantitative approach and convenience sample. The groups, control and study, obtained 20 volunteers. They were included in the study group amputees prosthetized unilateral transtibial, excluding those with other hip surgeries and lower limbs, and those who had pain before or during testing. The study was developed in the Human Movement Analysis Laboratory of the Department of the Federal University of Ceará Physiotherapy. It held the Postural Stability tests, considering the overall stability and anterior / posterior and average rates / side; SPA test (passive and active), with target angles of 45° and 60°; and dynamometry Isokinetic associated with surface electromyography for the ENM. All volunteers completed the study, performing all assessments proposed. The results showed reduced ENM adductor muscles amputee to compare them to the control group. The Postural Stability test confirmed the reduction of the balance in transtibial amputees in the mid / side index had the biggest difference when comparing their results with the control group. In the SPA test statistically significant differences were observed in the comparison between the study and control groups and in place between amputated and non amputated limb. It was concluded that transtibial amputees have reduced strength in both limbs, associated with increased activation of the adductor muscles of the residual limb, reducing its ENM and becoming a probable factor for its lower postural stability. There was no reduction in the SPA, so there is no evidence that there is impaired proprioception of these individuals.